Analyse du fonctionnement de collectifs d'enseignants : proposition méthodologique - Jean-François Marcel; Audrey Murillo (Université de Provence, 2014)
Based on teacher team studies and professional efficacy concept, this article aims at proposing a method of investigating teacher teams. A personalized questionnaire for each team under study points to two indications: team mobilization and diverging opinions about collaboration. The questionnaire tested on three teacher teams in agricultural schools shows the discriminating power of these indications which are linked to the team coordinator role and the self-perceived efficacy index of the team.